Vietnam’s capture fisheries labor shortage explored: difficulties and responses - To Van Phuong; Robert S. Pomeroy (Journal of Fisheries)
The fishing industry plays an essential role in Vietnam’s socioeconomic development, providing jobs to millions of workers. In recent years, fishing labor shortages have occurred on many fishing vessels in all capture fisheries, including small-scale and larger-scale fisheries in Vietnam. However, information pertaining to Vietnam’s fishing laborers has been limited for many years. In this study, a combination of secondary data methods and analysis of survey interviews with fishers who are fishing vessels’ owners and fisheries authorities in some key coastal provinces was used to answer the following questions: i) what are the difficulties in recruiting fishing labor in Vietnam’s capture fisheries? ii) How do fishing vessel owners respond to fishing labor’s shortages? Study results show many difficulties in crew labor issues in Vietnam in terms of finding crew members and maintaining minimum conditions for the number of workers on fishing vessels. Many reasons are found that cause the shortage of fishing laborers working on vessels. The owners of the fishing vessel have various ways to address this situation, including forcing fishing vessels to lie ashore or even go fishing in the case of labor shortage, switching to alternatives that require fewer human resources, actively seeking labor in other areas such as remote and mountainous areas, and increasing the share rate and deposit for fishing vessels fishing mates. Several solutions are proposed according to the results to overcome the labor shortage in Vietnam's capture fisheries.